The changing stratosphere - Mcelroy, Michael B.; Salawitch, Ross J.; Minschwaner, Kenneth (1992)
The current status of stratospheric research on stratospheric ozone is reviewed. Special attention is given to ozone chemistries in the upper and the lower stratosphere at the Antarctic, Arctic, and tropical latitudes, as well as at midlatitudes. The consequences these changes have on global climate are discussed in the framework of a one-dimensional radiative-convective model.